(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
COVID-19, caused by SARS-CoV-2, is primarily known as a respiratory illness; however, it has been increasingly recognized as a multi-organ disease with significant extrapulmonary manifestations. The virus affects various organ systems, including the cardiovascular, neurological, gastrointestinal, renal, and hematological systems, leading to complications such as myocarditis, thromboembolic events, encephalopathy, acute kidney injury, and gastrointestinal disturbances. The pathophysiological mechanisms underlying these manifestations involve direct viral invasion, immune dysregulation, endothelial dysfunction, and hyperinflammation.